The TCR Repertoire Reconstitution in Multiple Sclerosis: Comparing One-Shot and Continuous Immunosuppressive Therapies - Amoriello, Roberta; Greiff, Victor; Aldinucci, Alessandra; Bonechi, Elena; Carnasciali, Alberto; Peruzzi, Benedetta; Repice, Anna Maria; Mariottini, Alice; Saccardi, Riccardo; Mazzanti, Benedetta; Massacesi, Luca; Ballerini, Clara (Frontiers in Immunology, 2020)
Natalizumab (NTZ) and autologous hematopoietic stem cell transplantation (AHSCT) are two successful treatments for relapsing-remitting multiple sclerosis (RRMS), an autoimmune T-cell-driven disorder affecting the central nervous system that is characterized by relapses interspersed with periods of complete or partial recovery. Both RRMS treatments have been documented to impact T-cell subpopulations and the T-cell receptor (TCR) repertoire in terms of clone frequency, but, so far, the link between T-cell naive and memory populations, autoimmunity, and treatment outcome has not yet been established hindering insight into the post-treatment TCR landscape of MS patients. To address this important knowledge gap, we tracked peripheral T-cell subpopulations (naïve and memory CD4+ and CD8+) across 15 RRMS patients before and after two years of continuous treatment (NTZ) and a single treatment course (AHSCT) by high-throughput TCRß sequencing. We found that the two MS treatments left treatment-specific multidimensional traces in patient TCRß repertoire dynamics with respect to clonal expansion, clonal diversity and repertoire architecture. Comparing MS TCR sequences with published datasets suggested that the majority of public TCRs belonged to virus-associated sequences. In summary, applying multi-dimensional computational immunology to a TCRß dataset of treated MS patients, we show that qualitative changes of TCRß repertoires encode treatment-specific information that may be relevant for future clinical trials monitoring and personalized MS follow-up, diagnosis and treatment regimes.